Initial Invasive or Conservative Strategy in Heart Failure With Preserved Ejection Fraction and Coronary Artery Disease - Gu, Jun; Pan, Jian-an; Zhang, Jun-feng; Wang, Chang-qian (Frontiers in Cardiovascular Medicine, 2022)
Background: Among patients with heart failure with preserved ejection fraction (HFpEF) and coronary artery disease (CAD), whether clinical outcomes are better in those who receive an initial invasive strategy than in those who receive an initial conservative strategy is uncertain. Methods: Using data from heart failure cohort study, we analysed patients who had HFpEF and CAD amenable to the invasive intervention. We used propensity score matching of 1:1 ratio to compare the initial invasive strategy and the initial conservative strategy of medical therapy alone. The primary outcome was the composite endpoints of all-cause mortality or cardiovascular hospitalization. The secondary outcome was the all-cause mortality or cardiovascular hospitalization. Results: Of 1718 patients, 706 were treated with the invasive strategy and 1012 with the conservative strategy initially. Propensity score matching was used to assemble a matched cohort of 1320 patients receiving the invasive intervention (660 patients) or the medical therapy alone (660 patients). With a follow-up of 5 years, 378 (57.3%) in the invasive-strategy group and 403 (61.1%) in the conservative-strategy group reached the primary endpoint, there was no difference in the rate of the primary endpoint (P=0.162). The initial invasive strategy only improved the secondary outcome of cardiovascular hospitalization (P=0.035). And the multivariable Cox regression model revealed that anti-platelet therapy, angiotensin-converting enzyme inhibitor/angiotensin II receptor blocker (ACEI/ARB) or statin prescription was associated with a decreased risk of primary outcome. Conclusions: In this well-profiled, propensity-matched cohort of patients with HFpEF and CAD, the addition of invasive intervention to medical therapy did not improve long-term composite of all-cause mortality or cardiovascular hospitalization.